(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2025)
The hemostasis system plays a crucial role in maintaining blood fluidity and preventing excessive bleeding or thrombosis. Its functional characteristics undergo significant changes throughout different stages of human development, from the neonatal period to old age. These age-related variations are determined by the maturation and gradual decline of coagulation factors, anticoagulant mechanisms, platelet function, and fibrinolytic activity.